2006
DOI: 10.1161/01.hyp.0000244758.50351.29
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Systolic and Pulse Pressure in an Intercross Between Normotensive Inbred Rats

Abstract: Abstract-By continuous monitoring of abdominal aortic blood pressure via telemetry in conscious rats, we have observed that systolic, diastolic, and pulse pressures of male Brown-Norway rats were all significantly lower than that of male Wistar-Kyoto rats, despite the fact that all of the values in both strains were within normotensive ranges. Further analyses performed in 166 animals from the progeny of an F2 intercross between Brown-Norway and Wistar-Kyoto rats revealed that, despite a high correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Concerning the relationships among the other BP phenotypes, our results are consistent with those reported from an investigation carried out in rats [44], in which no phenotypic correlation was found for DBP-PP. This lack of correlations is also supported by some genetic studies [45,46], which showed that some loci influencing PP are different from the ones linked to either DBP or SBP.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the relationships among the other BP phenotypes, our results are consistent with those reported from an investigation carried out in rats [44], in which no phenotypic correlation was found for DBP-PP. This lack of correlations is also supported by some genetic studies [45,46], which showed that some loci influencing PP are different from the ones linked to either DBP or SBP.…”
Section: Discussionsupporting
confidence: 92%
“…A PA11-C40 pressure telemeter (Data Sciences International, St Paul, MN, USA) was implanted s.c. in the left flank and secured by a purse string suture. The 10 cm cannula was inserted in the femoral artery and advanced into the aorta to the level of the renal arteries, leaving slack to accommodate growth [16,27]. After recovery (∼2 weeks) and acquisition of a control record, all rats were subjected to the 2K1C procedure [27].…”
Section: Methodsmentioning
confidence: 99%
“…The 10 cm cannula was inserted in the femoral artery and advanced into the aorta to the level of the renal arteries, leaving slack to accommodate growth [16,27]. After recovery (∼2 weeks) and acquisition of a control record, all rats were subjected to the 2K1C procedure [27]. After recovery (∼2 weeks) and acquisition of another data record, rats were assigned to one of four experimental groups: intact with normal salt (IN-N Chronic data acquisition Metabolic measurements (24 h food and fluid intake, urine output) plus 24 h BP records were acquired at control, after 2K1C, and weekly thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely appreciated that male and female hearts are different both at baseline and in response to numerous stimuli (for a recent review see Llamas et al 2 ). In general, male hearts respond less well to pressure or volume overload, to myocardial infarction (MI), and to aging.…”
mentioning
confidence: 99%